2018
DOI: 10.1111/jphs.12245
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy drive-thru service in Jordan: assessing customers' awareness, perceptions and factors affecting the use of this service

Abstract: Objectives In Jordan, drive‐thru pharmacy service has recently been introduced representing a new trend in community pharmacy services. This study aimed to evaluate pharmacy customers' awareness and perceptions towards the drive‐thru service to unveil important information regarding such service. Methods A Self‐administered questionnaire was used in this cross‐sectional study which was conducted in Amman‐Jordan between April and August 2017. A Self‐administered questionnaire was used to evaluate pharmacy custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 15 publications
(40 reference statements)
17
29
2
Order By: Relevance
“…Malewski et al (2015) found a significant difference between residence region (urban and suburban) regarding customer-pharmacist trust, customer service, and pharmacy accessibility. Moreover, Abu Hammour et al (2019) stated that patients in Jordan with busy lifestyle showed higher tendency to use the drive-thru service than others, which contradict the results of this research.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Malewski et al (2015) found a significant difference between residence region (urban and suburban) regarding customer-pharmacist trust, customer service, and pharmacy accessibility. Moreover, Abu Hammour et al (2019) stated that patients in Jordan with busy lifestyle showed higher tendency to use the drive-thru service than others, which contradict the results of this research.…”
Section: Discussioncontrasting
confidence: 89%
“…Pharmacy easy accessibility is the highest item rated by the respondents while availability of valet parking service was the lowest item rated among the convenience dimensions. It should be clear that the idea of valet services are relatively new to the Jordanian society and used to be a service only provided by 5 stars hotels and restaurants (Abu Hammour et al, 2019). Wazaify et al (2008) showed that only 26% of respondents visit the same pharmacy because of its convenience location and proximity to their resident or work.…”
Section: Discussionmentioning
confidence: 99%
“…52 In Jordan, drive-through pharmacy services have recently been introduced representing a new trend in community pharmacy services with positive customer awareness and perceptions towards the service. 53 Although of course the model limits the 'sit-down' counseling deemed as a higher order role of pharmacists, in Jordan, this service appeared well received particularly in a certain subset of customers, but concerns regarding proper counseling represented the main disadvantage of the service. 43 About 50% of the participants in this study believed that they should be allowed to sell medications for coronavirus management via the drive-through service available in some chain pharmacies in Jordan.…”
Section: Tablementioning
confidence: 99%
“…They found that the drive-thru service is mostly used by busy customers. [ 4 ] However, some concerns about poor commutation between customers and pharmacists and increase the risk of medication error are expected reported complications of this system were reported. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%